MANAJEMEN PERUBAHAN DALAM UPAYA MENINGKATKAN KINERJATENAGA PENDIDIK DI SMA SANTO IGNASIUS SINGKAWANG - Sainon, Sainon; Wahyudi, Wahyudi; Usman, Andi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSanto Ignasius Senior High School that is located in Singkawang city is a school managed by a foundation named Yayasan Pengabdi untuk Sesama Manusia (YPSM). Since 2002, the top management of Ignasius Senior High School (ISHS) have built the building and developed the system. New and permanent classrooms, large library, and modern laboratories indicates that change. The new students come to Ignasius have better quality than before. Teachers and students develop their capability year by year. These things motivated the researcher to research how the principle manages that change, especially to improve teachers performance.This research is a descriptive qualitative research. The researcher comes to Ignasius SHS several times for observation about management of chage hold by principal. The researcher interviews some of the teacher and students, and principal as data resources. When the data have good validity and reability, the researcher analyse them qualitatively and then describes the result of analysis. First of all, the researcher found that Ignasius SHS has developed phisically. With good cooperation between the principal and the leader of YPSM, at last they could build new and permanent classrooms, compliting the learning teaching facilities, and proportional parking area. Based the data, the change is not only happens phisically, but also on the system. This is proved by notula, the minutes of meetings, researcher got from administration office.Second, the most important factor about change happens in Ignasius SHS is management by principle. The principle has done planning, coordinating, and also evaluating all programs. The principle also made good cooperation with all stakeholders so Ignasius SHS can reach that achievement. Third, changes happen in Ignasius SHS significantly influence teachers achievement. When principle doing open management and focusing on better performance, it raises people trust. The people will send their children to Ignasius year by year. As a result, management has better capability to pay teachers salary.Keywords:Change Management, Performance Improvement, Teachers Â